COMPLIANCE ANALYSIS OF MEDICAL RECORD FILLING AT KALISAT HOSPITAL JEMBER - Tandy, Dinnya Yesica; Witcahyo, Eri; Utami, Sri (Preventif : Jurnal Kesehatan Masyarakat, 2018)
Background & Objective : Hospital quality services is not only from medical services but also the supportservices, one of them is the completeness of medical records. The medical record filling issues areincompleteness and non-spesific diagnostic writing from the doctor. In 2016, the completeness of medicalrecords in Kalisat Hospital reaches 61,43%. Less motivation and performance may be the cause of doctorsand nurses compliance in medical records filling. This study aims to analyze determinants that relate to thecompliance of medical records filling in Kalisat Hospital. Material and Method: This study usesdescriptive research with a sample size of 47 people. The data is also presented in Scatter diagram to find thecorrelation of two variables. Result: The result showed that the majority of respondents had good knowledgeof medical records, more respondents worked for 5 – 10 years, and majority worked in early adult age 25 - ≥40 years old. The majority of respondents had a good attitude and motivation. The majority of respondentshad a good response about the filling medical records leadership, a good rewards, but a less response aboutwork design in Kalisat Hospital. The scatter diagram showed that there were a positive correlation betweenknowledge, attitude, motivation, leadership, and rewards variables for the compliance of medical recordfiles. Conclusion: Based on the study, it can be concluded that there is a positive correlation betweenknowledge, attitude, motivation, leadership, and reward with compliance of medical records file in KalisatHospital Jember.